Humane slaughter of swine - Ricci, Gisele Dela; Costa, Osmar Antonio Dalla (Revista de Ciências Agroveterinárias, 2015)
The aim of this review was to describe the procedures related to pre-slaughter management to enable the humane slaughter of pigs. The pre-slaughter management is defined as the set of practices for them from the property to the fridge. These procedures have received more attention from the moment that stress was diagnosed among the main responsibilities for losses related to meat quality and economy of the entire system. The shipment, transportation, landing, fasting, water diet, the types and adequacy of stunning and bleeding efficiency are factors that need training for producers, employees and others involved with the production chain for pigs to keep them from interfering with the welfare of these animals.